PELATIHAN PEMBUATAN KEMASAN (PACKAGING) UNTUK MENINGKATKAN PEMASARAN PRODUK UMKM MARNING DI DESA MARGOJADI - Lathifah Lathifah; Lulud Oktaviani; Suaidah Suaidah; Ahmad Ari Aldino; Nabila Arra Putri (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
The people of Mesuji regency in Margojadi village have corn crops, during this pandemic corn sales decreased, resulting in cheap corn prices. Farmers feel a loss because the harvest model is not in accordance with the buying and selling price. With such obstacles, mothers and the surrounding community took the initiative to make snacks with processed corn called marning. The process of making marning is raw corn dissassemled from the bongkolnya, after which the corn is washed thoroughly and dried until dry. When the corn is dry, the frying process is carried out until the corn expands and is yellowish in color, remove and drain the corn that has been fried with newspaper coated to absorb oil. When the corn is cold the corn is given a salty, sweet, and spicy seasoning. Sales are only around the Mesuji area so that revenue is still mediocre. The existence of this PKM is to help MESUJI MSME efforts to make packaging more attractive, to increase the marketing of marning products in the village of Margojadi Mesuji Timur. Training to make this packaging by means of lectures, tutorials, and discussions with workers to increase marning production and increase sales results and economic sectors in Mergojadi village for the better.